The use of seawater as a source of magnesium chloride in magnesium ammonium phosphate (MAP)treatment method - Nur Ain Farhana, Ghani (2013)
POME is a thick brownish liquid that contains high solids, oil and grease (O&G), chemical oxygen demand (COD) and Biochemical Oxygen Demand (BOD) content. When POME discharged untreated into watercourses, it will adversely affect the aquatic life and domestic water supply. POME is commonly treated using conventional systems, however, these systems failed to utilize the nutrient contained within POME. The use of several magnesium and phosphate based chemicals or magnesium ammonium phosphate (MAP) precipitation method have been shown to provide an effective treatment of wastewater containing substantial amount of nutrients. MAP precipitation method extract precious nutrient in the form MAP crystals. MAP display excellent fertilizer quality when compared to commercially available fertilizers. The extraction of MAP although rapid, however, is rather costly as it involves several different chemicals. Alternatives to magnesium based chemicals such as seawater may be used to reduce operational cost. This study focuses on treatment of P0MB from Sime Darby Jabor Palm Oil Mill using MAP precipitation method. MgCl2 and Na2HPO4 are mixed with raw POME. Seawater was also used as substitute as M902. The results indicated that, MAP precipitation method can be used to treat POME and at the same time produced of high quality fertilizer. About 70% to 80% Mg and COD concentrations were removed. A maximum of 23 g of MAP were extracted for each 250 ml of POME used. However, the water contents of the precipitates were very high, particularly when extracted using seawater thus, further drying and dewatering are required.